Bioactive peptides identification and nutritional status ameliorating properties on malnourished rats of combined eel and soy-based tempe flour - Sabrina, Nindy; Rizal, Mochammad; Nurkolis, Fahrul; Hardinsyah, Hardinsyah; Tanner, Melvin Junior; Gunawan, William Ben; Handoko, Matthew Nathaniel; Mayulu, Nelly; Taslim, Nurpudji Astuti; Puspaningtyas, Dwi Sari; Noor, Sutamara Lasurdi; Yusuf, Vincentius Mario; et al. (Frontiers in Nutrition, 2022)
Background and aims A combined eel and soy-based tempe (CEST) flour is rich in nutrients, especially its high amino acid content in which bioactive peptides (BPs) are expected to be found. Hence, this research aimed to identify the BPs of CEST flour and CEST supplementation’s effect on improving nutritional status biomarkers by ameliorating serum protein, hemoglobin, and IGF-1 of malnourished rats. Methods CEST flour with a ratio of eel and soy-based tempe of 1:3.5 was produced by applying the oven drying method. Amino acid sequences from six BPs were analyzed using a protein sequencer and spectrometer-electrospray ionization (MS-ESI). A total of thirty malnourished male Rattus norvegicus aged 3–4 weeks were given low-protein (LP; 4% w/w protein) diet treatment for 4 weeks. Afterward, rats were divided into 3 groups of 10 rats. Group A and B remained on a low-protein diet for 4 weeks, receiving an LP diet and getting doses of CEST of 100 and 200 mg/kg BW, respectively, via oral. Group C or control was given a Normal-protein (NP) diet (23% w/w of protein) and was allowed to feed ad libitum during the trial period without a dose of CEST. Results Six bioactive peptides were found, with WMGPY being the most abundant, along with a DPPH radical scavenging activity of 5.0 mg/mL. The results showed that serum protein, hemoglobin, and IGF-1 of group B were significantly higher compared to groups A and C (p = 0.0021). CEST dose of 200 mg/kg BW was more effective to increase serum levels of protein (p = 0.0052), hemoglobin, and IGF-1 (p < 0.0001) compared to a 100 mg/kg BW dose. Conclusion This indicates that the CEST flour has six bioactive peptides, which may contribute to the improvement of nutritional status biomarkers. To establish its potential impact, a human clinical study is urgently needed.